Tupiperla (Plecoptera: Gripopterygidae) from southwestern Minas Gerais State, Brazil, with the description of Tupiperla amorimi n.sp. - Froehlich, Claudio G. (Zootaxa, 2016)
The genus Tupiperla Froehlich 1969 occurs in Brazil from Bahia and Goiás states south to Santa Catarina State and also in nearby areas of Misiones Province, Argentina and southern Paraguay. Recently, Duarte et al. (2014a, 2014b) described two new species from Bahia State. With the present new species, the number of known species of this genus is currently 19.